Media Studies’ Approach In “The Crowd” Problems - Kien, Phan Van; Hoang Long, Vu (VNU Journal of Science: Policy and Management Studies, 2020)
In this article, we aim to analyze particular conditions of the media landscape in recent days Vietnam – which is characterized by the domination of mass media and social media in constituting public opinions – that significantly affect collective actions from the online citizens. By using the concept “collective actions”, we design to reconceptualize the concept of “the crowd” which is used commonly to assert the detrimental effects of online citizens’ actions toward heated public debates nowadays. Through the framework of media and journalism studies, we suppose that the contemporary media landscape is not the same as the social situation in approximately 150 years ago when Western scholars first used this concept. Moreover, we intend to provide the framework of Affect Studies in approaching online citizens’ practices that considerably influences the field of media studies in particular and Social Sciences and Humanities in general.